Inverse medium scattering problems with Kalman filter techniques. (1st September 2022) - Furuya, Takashi; Potthast, Roland
Abstract: We study the inverse medium scattering problem to reconstruct the unknown inhomogeneous medium from the far field patterns of scattered waves. The inverse scattering problem is generally ill-posed and nonlinear, and the iterative optimization method is often adapted. A natural iterative approach to this problem is to place all available measurements and mappings into one long vector and mapping, respectively, and to iteratively solve the linearized large system equation using the Tikhonov regularization method, which is called Levenberg–Marquardt scheme. However, this is computationally expensive because we must construct the larger system equations when the number of available measurements is increasing. In this paper, we propose two reconstruction algorithms based on the Kalman filter. One is the algorithm equivalent to the Levenberg–Marquardt scheme, and the other is inspired by the extended Kalman filter. For the algorithm derivation, we iteratively apply the Kalman filter to the linearized equation for our nonlinear equation. By applying the Kalman filter, our proposed algorithms sequentially update the state and the weight of the norm for the state space, which avoids the construction of large system equation, and retains the information of past updates. Finally, we provide numerical examples to demonstrate the proposed algorithm.